Safety Analysis of Fiberoptic Bronchoscopy in Children - Liu, Jiandong; Li, Xueting (Pacific International Journal, 2024)
Fiberoptic bronchoscopy (FOB) is a crucial procedure in pediatric pulmonology, providing significant diagnostic and therapeutic benefits. This study evaluates the safety of FOB in children at The People’s Hospital of Keyouqianqi, Inner Mongolia. A retrospective analysis was conducted on the medical records of 10 pediatric patients who underwent FOB between 2018 and 2023. The study assessed the incidence, types, and severity of complications, as well as factors contributing to these complications. The findings indicated a complication rate of 20%, with transient hypoxia and mild bleeding as the most common minor complications. No severe complications, such as severe bleeding, bronchospasm, or pneumothorax, were observed. Statistical analysis revealed that procedural factors significantly influenced the occurrence of complications. The study concludes that FOB is generally safe for pediatric patients, with a low incidence of severe complications. Recommendations include enhancing training and protocols, continuous monitoring, preventive measures, further research, and policy development to ensure the highest standards of patient care.